Sheikh Kamal sports complex: Abahoni ground, Shat Mosjit Road, Dhanmondi, Dhaka - Rahman, Md. Shafiur (BRAC University, 2015)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2015.